2008
DOI: 10.1111/j.1471-4159.2008.05334.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y stimulates retinal neural cell proliferation – involvement of nitric oxide

Abstract: Neuropeptide Y (NPY) is a 36 amino acid peptide widely present in the CNS, including the retina. Previous studies have demonstrated that NPY promotes cell proliferation of rat post‐natal hippocampal and olfactory epithelium precursor cells. The aim of this work was to investigate the role of NPY on cell proliferation of rat retinal neural cells. For this purpose, primary retinal cell cultures expressing NPY, and NPY Y1, Y2, Y4 and Y5 receptors [Álvaro et al., (2007) Neurochem. Int., 50, 757] were used. NPY (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 81 publications
(102 reference statements)
6
46
0
Order By: Relevance
“…In fact, a link between NO and the physiological effects of NPY was suggested by Morley et al (35), who showed that a low dose of NPY was able to increase NOS expression in the hypothalamus by 147% and that an NPY-induced increase in food intake was mediated via NOS. More recently, Alvaro et al (23) showed that NOS was involved in mediating the NPY-induced proliferation of retinal neural cells, further supporting our hypothesis. Through the use of pharmacological, immunocytochemical, and live cell imaging techniques, we describe the involvement of NO signaling in mediating the neuroproliferative effect of NPY on cultures derived from the postnatal rat hippocampus.…”
Section: Neuropeptide Y (Npy)supporting
confidence: 87%
See 4 more Smart Citations
“…In fact, a link between NO and the physiological effects of NPY was suggested by Morley et al (35), who showed that a low dose of NPY was able to increase NOS expression in the hypothalamus by 147% and that an NPY-induced increase in food intake was mediated via NOS. More recently, Alvaro et al (23) showed that NOS was involved in mediating the NPY-induced proliferation of retinal neural cells, further supporting our hypothesis. Through the use of pharmacological, immunocytochemical, and live cell imaging techniques, we describe the involvement of NO signaling in mediating the neuroproliferative effect of NPY on cultures derived from the postnatal rat hippocampus.…”
Section: Neuropeptide Y (Npy)supporting
confidence: 87%
“…Recently, Lou et al (42) have shown that the effects of NO on neural stem/precursor cells differ significantly depending on whether it was released extracellularly (antiproliferative) or intracellularly (proliferative). Although the involvement of NO mechanisms was thought to underlie the proliferative effect of NPY in retinal neural cells (23), our results are the first to demonstrate that intracellular NO produced by nNOS signals the complete Y 1 receptor-mediated proliferative effect of NPY on hippocampal nestin ϩ precursors, whereas extracellular NO had the opposite antiproliferative effect. We also show that ERK1/2 activation by NPY is solely mediated via NOS-NO mechanisms.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations